2012
DOI: 10.1080/15332640.2012.735182
|View full text |Cite
|
Sign up to set email alerts
|

The Social and Environmental Context of Cross-Border Drug Use in Mexico: Findings from a Mixed Methods Study of Young Injection Drug Users Living in San Diego, CA

Abstract: We report the results of qualitative (n=19) and quantitative (n=545) interviews with young injection drug users (IDUs) in San Diego, California, USA about their experiences using drugs in Tijuana, Mexico, and associated risks for HIV infection. Young IDUs who have ever traveled to Mexico (n=365) used a variety of injection (54%) and non-injection (30%) drugs there, and appear to be heavier users than those who have never traveled to Mexico. Sociocultural themes influencing drug use in Mexico included: interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
(20 reference statements)
2
21
0
Order By: Relevance
“…This could impact their risk for acquiring these infectious diseases (Rothenberg et al, 2000, 1998). PWIDs’ travel to Mexico because of a perception that it is easier to evade criminal penalties in the US, as demonstrated in the current study, or to obtain lower-cost or more available drug supplies, as shown in previous work (Wagner et al, 2012), demonstrates the continued need for laws in the US that provide alternatives to incarceration and that connect people to services (e.g., evidence based drug treatment) while keeping them connected to their support networks.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This could impact their risk for acquiring these infectious diseases (Rothenberg et al, 2000, 1998). PWIDs’ travel to Mexico because of a perception that it is easier to evade criminal penalties in the US, as demonstrated in the current study, or to obtain lower-cost or more available drug supplies, as shown in previous work (Wagner et al, 2012), demonstrates the continued need for laws in the US that provide alternatives to incarceration and that connect people to services (e.g., evidence based drug treatment) while keeping them connected to their support networks.…”
Section: Discussionsupporting
confidence: 67%
“…Both cities are located on a major international drug trafficking route that runs from the Andean region in South America to the United States, making drugs such as heroin, methamphetamine, and cocaine abundant in both cities (Bucardo et al, 2005). Approximately 10,000 people who inject drugs (PWIDs) reside in Tijuana, with many more crossing the border from San Diego, reportedly to use and buy illicit drugs because of lower prices, easier access, and to avoid facing legal penalties in the United States (Morales, Lozada, Magis, & Saaverda, 2004; Volkmann et al, 2011; Wagner et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high risk of drug use among transnational Mexicans, defined as individuals who have resided in both Mexico and the United States, may have negative effects on the health and well-being of residents in both countries [5-7]. Emerging evidence has suggested that Mexican migrants who come to the United States increase their drug use while in the United States and those who return to Mexico have higher rates of substance problems [4,5] that often go untreated, compared to the nonmigrant population [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Concern about bi-directional transmission of HIV and other infectious diseases at the US-Mexico border has inspired research to elucidate the social and environmental factors contributing to increased risk for HIV in this and other border regions [29, 30, 33, 34]. Social network-based approaches, which examine the composition and function of social relationships (including drug using relationships), are ideal for helping to uncover the mechanisms underlying HIV transmission in environments characterized by high levels of mobility and population mixing [35].…”
Section: Introductionmentioning
confidence: 99%